2014
DOI: 10.1124/jpet.114.213991
|View full text |Cite
|
Sign up to set email alerts
|

Lubiprostone Prevents Nonsteroidal Anti-Inflammatory Drug–Induced Small Intestinal Damage by Suppressing the Expression of Inflammatory Mediators via EP4 Receptors

Abstract: Lubiprostone, a bicyclic fatty acid derived from prostaglandin E 1 , has been used to treat chronic constipation and irritable bowel syndrome, and its mechanism of action has been attributed to the stimulation of intestinal fluid secretion via the activation of the chloride channel protein 2/cystic fibrosis transmembrane regulator (ClC-2/CFTR) chloride channels. We examined the effects of lubiprostone on indomethacin-induced enteropathy and investigated the functional mechanisms involved, including its relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 43 publications
(58 reference statements)
8
38
0
Order By: Relevance
“…Other prostanoids such as ONO-NT-012 (an EP3 agonist) and ONO-AE1-329 (an EP4 agonist) provided dose-dependent protection against indomethacin-induced intestinal damage, whereas neither 17-phenyl PGE 2 (an EP1 agonist) nor butaprost (an EP2 agonist) had any effect on these lesions. Lubiprostone, a bicyclic fatty acid derived from PGE 1 [67], also prevented these lesions in the small intestine, and this effect was significantly abrogated by the co-administration of AE3-208, an EP4 antagonist, suggesting the involvement of EP4 receptors in these protective effects [57]. These findings support the importance of EP4 receptors in the protective effects of PGE 2 against NSAID-induced intestinal damage.…”
Section: Roles Of Ep Receptor Subtypes In Protective Effects Of Pge2supporting
confidence: 65%
See 3 more Smart Citations
“…Other prostanoids such as ONO-NT-012 (an EP3 agonist) and ONO-AE1-329 (an EP4 agonist) provided dose-dependent protection against indomethacin-induced intestinal damage, whereas neither 17-phenyl PGE 2 (an EP1 agonist) nor butaprost (an EP2 agonist) had any effect on these lesions. Lubiprostone, a bicyclic fatty acid derived from PGE 1 [67], also prevented these lesions in the small intestine, and this effect was significantly abrogated by the co-administration of AE3-208, an EP4 antagonist, suggesting the involvement of EP4 receptors in these protective effects [57]. These findings support the importance of EP4 receptors in the protective effects of PGE 2 against NSAID-induced intestinal damage.…”
Section: Roles Of Ep Receptor Subtypes In Protective Effects Of Pge2supporting
confidence: 65%
“…An RT-PCR analysis revealed that neither iNOS nor TNFα mRNAs was detected in the normal intestinal mucosa, but they were potently expressed in the mucosa as early as 3 h after the administration of indomethacin [56,57]. The upregulated expression of iNOS mRNA was similarly observed in the intestinal mucosa of animals given SC-560, but not rofecoxib [16].…”
Section: Functional Alterations In the Small Intestine After Administmentioning
confidence: 99%
See 2 more Smart Citations
“…Lubiprostone may be protective against nonsteroidal anti-inflammatory drug (NSAID) induced enteropathy via the EP4-dependent pathway. In rats, administration of lubiprostone significantly reduced indomethacin-induced damage to the small intestine, an effect that was eliminated in the presence of a selective EP4 antagonist [Hayashi et al 2014]. In a mouse model of cystic fibrosis, administration of lubiprostone increased proximal-and mid-intestinal mucin secretion [De Lisle, 2012].…”
Section: Lubiprostonementioning
confidence: 99%